Space geodetic tools provide early warnings for earthquakes and volcanic eruptions. Issue 4 (20th April 2017) - Aoki, Yosuke
Abstract: Development of space geodetic techniques such as Global Navigation Satellite System and Synthetic Aperture Radar in last few decades allows us to monitor deformation of Earth's surface in unprecedented spatial and temporal resolution. These observations, combined with fast data transmission and quick data processing, enable us to quickly detect and locate earthquakes and volcanic eruptions and assess potential hazards such as strong earthquake shaking, tsunamis, and volcanic eruptions. These techniques thus are key parts of early warning systems, help identify some hazards before a cataclysmic event, and improve the response to the consequent damage. Key Points: Space geodesy revolutionized earthquake and volcano studies Space geodetic techniques contribute to early warning of earthquakes and volcanic eruptions Space geodetic techniques can identify hazards quickly after an earthquake or volcanic eruption